2021
DOI: 10.1073/pnas.2022248118
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin is essential for maintaining quiescence in vascular endothelial cells

Abstract: Thrombomodulin (TM) is a thrombin receptor on endothelial cells that is involved in promoting activation of the anticoagulant protein C pathway during blood coagulation. TM also exerts protective anti-inflammatory properties through a poorly understood mechanism. In this study, we investigated the importance of TM signaling to cellular functions by deleting it from endothelial cells by CRISPR-Cas9 technology and analyzed the resultant phenotype of TM-deficient (TM−/−) cells. Deficiency of TM in endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 37 publications
1
58
0
Order By: Relevance
“…In this respect, high thrombomodulin is associated with severe disease here and has predictive value for mortality in COVID-19 infection elsewhere [15,57]. Our results also demonstrated a concomitant increase in plasma sEPCR and thus suggest that endothelial expression of both receptors of the protein C pathway were affected, pointing towards a potentially impaired ability of the endothelium to generate and mediate APC cellular functions which reportedly reduce inflammation, apoptosis, and stabilize endothelial and epithelial barriers [40,41]. While most studies show mild changes in PC levels [4À8], a recent paper reported lower protein C in COVID-19 patients, resulting in an acquired protein C deficiency-like picture that may contribute to development of a thrombogenic state and worsening of patient`s clinical condition [60].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In this respect, high thrombomodulin is associated with severe disease here and has predictive value for mortality in COVID-19 infection elsewhere [15,57]. Our results also demonstrated a concomitant increase in plasma sEPCR and thus suggest that endothelial expression of both receptors of the protein C pathway were affected, pointing towards a potentially impaired ability of the endothelium to generate and mediate APC cellular functions which reportedly reduce inflammation, apoptosis, and stabilize endothelial and epithelial barriers [40,41]. While most studies show mild changes in PC levels [4À8], a recent paper reported lower protein C in COVID-19 patients, resulting in an acquired protein C deficiency-like picture that may contribute to development of a thrombogenic state and worsening of patient`s clinical condition [60].…”
Section: Discussionsupporting
confidence: 54%
“…Whether these changes translate in upregulation of TF protein in the lung, and its cellular distribution remained elusive thus far. Another recent study reported a reduction in pulmonary transcriptional levels of thrombomodulin [39], a major endothelial cell anticoagulant [40,41]. Likewise, it is unknown whether thrombomodulin expression in the endothelial cell of small vessels, where it normally resides [41] is downregulated in the lung of patients who succumbed from the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombomodulin (TM) is an EC surface receptor that facilitates thrombin‐induced activation of protein C on EC surfaces 26 . Recently, Giri et al reported that TM plays a key role in maintaining EC quiescence 27 . Of particular relevance, they showed that VWF expression and secretion was markedly increased in TM‐deficient ECs.…”
Section: Resultsmentioning
confidence: 99%
“…26 Recently, Giri et al reported that TM plays a key role in maintaining EC quiescence. 27 Of particular relevance, they showed that VWF expression and secretion was markedly increased in TM-deficient ECs.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Besides, thrombomodulin (TM) is an endothelial cell transmembrane glycoprotein that is only released upon direct endothelial disruption 23 . soluble thrombomodulin (sTM) is released into plasma during in ammation, presumably due to cleavage from endothelial cells by neutrophil-derived enzymes 24,25 .…”
Section: Discussionmentioning
confidence: 99%